The essence of the emerging markets' investment risk: Comparative analysis of American and Central European convertible bond issuers - Jakub Marszałe (Comparative Economic Research. Central and Eastern Europe, 2015)
This paper attempts to identify the determinants of credit ratings for debt instrument issuers in the so-called emerging markets. The study was conducted on the sample of convertible bonds issuers in 2001-2012, half of which originated from Central and Eastern Europe, while the rest were U.S. operators. The analysis is focused exclusively on pairs of bonds with the same rating given by the British Fitch agency, which specialises in analysing Central and East European markets. The conducted studies show that solvency risk, interpreted as indebtedness, financial leverage and current solvency, is a major difference between the two groups of bonds. Changes in indebtedness, i.e. in assets held by foreign investors, are apparently the reasons of higher requirements for issuers from the emerging markets.
Keywords: 330; emerging market; convertible bond; rating; financing